2021
DOI: 10.3389/fpls.2021.650955
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Pretreatment Confers Heat Tolerance and Repression of Heat-Induced Senescence in Tomato Through the Modulation of ABA- and GA-Mediated Pathways

Abstract: Heat stress and abscisic acid (ABA) induce leaf senescence, whereas melatonin (MT) and gibberellins (GA) play critical roles in inhibiting leaf senescence. Recent research findings confirm that plant tolerance to diverse stresses is closely associated with foliage lifespan. However, the molecular mechanism underlying the signaling interaction of MT with GA and ABA regarding heat-induced leaf senescence largely remains undetermined. Herein, we investigated putative functions of melatonin in suppressing heat-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(83 citation statements)
references
References 94 publications
2
78
1
2
Order By: Relevance
“…Similar results were reported in kiwifruit seedlings [ 44 ] and basil plants [ 45 ] under salinity stress. In our experiments, pretreatment with 100 µmol MT also increased the endogenous MT level during heat stress ( Figure 5 ), consistent with Xu et al [ 25 ] and Jahan et al [ 46 ] in cucumber and tomato plants, respectively, during heat stress, and this could have contributed to augmenting the antioxidant defense mechanisms. The present study revealed a significant decrease in the PAs (Put, Spd, and Spm) due to heat stress.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were reported in kiwifruit seedlings [ 44 ] and basil plants [ 45 ] under salinity stress. In our experiments, pretreatment with 100 µmol MT also increased the endogenous MT level during heat stress ( Figure 5 ), consistent with Xu et al [ 25 ] and Jahan et al [ 46 ] in cucumber and tomato plants, respectively, during heat stress, and this could have contributed to augmenting the antioxidant defense mechanisms. The present study revealed a significant decrease in the PAs (Put, Spd, and Spm) due to heat stress.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, we can confirm that sufficient overexpression of SlBAG2 and SlBAG5b is beneficial for dark-induced stress tolerance. Although many efforts have been made to investigate senescence [ 39 , 55 ], the exact mechanisms underlying this event are not well understood [ 1 ]. Our evidence provides a clue for the function of these genes in the regulation of dark-induced, and probably natural, senescence [ 12 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Leaf senescence is a fine regulatory mechanism caused by multiple internal factors, such as cell death, plant hormones, nutrient deficiency, senescence related genes, and environmental factors, such as drought, high temperature, salinity, weak light and darkness, and so on [ 1 ]. The change of leaf color is the most obvious trait of leaf senescence, and the internal structure of leaves changes obviously during senescence, which is manifested in decreased chlorophyll content and abnormal chloroplast structure [ 1 ]. Therefore, the most significant feature of leaf senescence is the process of chlorophyll degradation.…”
Section: Introductionmentioning
confidence: 99%
“…We still do not know how H2S affects carbohydrate metabolism under heat stress and its relationship with melatonin. Melatonin is known as a biopromoter as it regulates numerous physiological methods and improves heat stress resistance in plants [74,75]. It is a small molecular weight indoleamine hormone explicitly being measured as a candidate phytohormone due to its various responses under biotic and abiotic stresses.…”
Section: Discussionmentioning
confidence: 99%